Attenuation of outside noise by shotblasting helmets - Żera, J.; Młyński, R. (Archives of Acoustics, 2004)
Abrasive blasting is a technological process in which forcibly propelling a stream of abrasive material is used to clean or prepare a surface. Among various physical and chemical hazards related to this process a shotblasting operator is exposed to high levels of noise. Regardless of the fact that there are no requirements to measure and report the attenuation of high level of blasting noise, manufacturers often face a question to which extent shotblasting helmets protect the operator from noise. Currently the well developed method for measuring the noise attenuation of shotblasting helmets is neither given in EN 271 standard dealing with the construction of helmets nor in EN 458 series of standards dealing with requirements for hearing protective devices. The purpose of this paper is to present the method of measurements of the noise attenuation provided by the shotblasting helmet. Keywords: noise attenuation, measurements on subjects, measurements on dummy head and torso, shotblasting helmets.